The Gateway to Computer Science Excellence

0 votes

If in a $\Delta ABC$, $\angle B = \frac{2 \pi}{3}$, then $\cos A + \cos C$ lies in

- $[\:- \sqrt{3}, \sqrt{3}\:]$
- $(\: – \sqrt{3}, \sqrt{3}\:]$
- $(\:\frac{3}{2}, \sqrt{3}\:)$
- $(\:\frac{3}{2}, \sqrt{3}\:]$

+1 vote

**Answer: $\mathbf A$**

We have:

$\mathrm {\angle A + \angle B + \angle C } = \pi \;\text{(By angle sum property of $\Delta$)}$

$\Rightarrow \mathrm{\angle A + \dfrac{2\pi}{3} + \angle C}=\dfrac{\pi}{3}$

Now, We know that:

$\mathrm{\cos A + \cos C = 2\cos\frac{A+C}{2}.\cos\frac{A-C}{2}}$

$\Rightarrow \mathrm{\cos A + \cos C = 2\cos\frac{\pi}{6}.\cos\frac{A-C}{2}} = 2\times \frac{\sqrt3}{2}\cos\frac{A-C}{2} = \sqrt3\cos\frac{A-C}{2}$

$\Rightarrow \mathrm{\cos A + \cos C=\sqrt3\cos\frac{A-C}{2}} $

We know that:

$-1 \le\cos \theta \le1, \;\forall \theta$

$\mathrm{\Rightarrow -1\le \cos\big (\frac{A-C}{2} \big )\le1}$

$\mathrm{\Rightarrow -\sqrt3\le \sqrt 3\cos\big (\frac{A-C}{2} \big )\le \sqrt3}$

$\Rightarrow \text {Range} = [-\sqrt3, \;\sqrt3]$

$\therefore \mathbf A$ is the right answer.

52,375 questions

60,574 answers

201,979 comments

95,389 users